If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8t + -2 = 33 + t Reorder the terms: -2 + 8t = 33 + t Solving -2 + 8t = 33 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -2 + 8t + -1t = 33 + t + -1t Combine like terms: 8t + -1t = 7t -2 + 7t = 33 + t + -1t Combine like terms: t + -1t = 0 -2 + 7t = 33 + 0 -2 + 7t = 33 Add '2' to each side of the equation. -2 + 2 + 7t = 33 + 2 Combine like terms: -2 + 2 = 0 0 + 7t = 33 + 2 7t = 33 + 2 Combine like terms: 33 + 2 = 35 7t = 35 Divide each side by '7'. t = 5 Simplifying t = 5
| 2k+2=-1313k | | 4K=-9k | | 144=-2-6(6+10) | | 130=3x+2y | | 5x+1+4=11+9x | | 3m+2m+4n+3n= | | 9/4x=1/16 | | 2/3x=140 | | 1=12x-8 | | 5x+8=6x-18 | | 10/9c=-81 | | P-3.2=7.6 | | 7.3y-5.8=51.9 | | 53-2x=5x-17 | | 15+9n=9-n | | 2(7x+2)=-12 | | 2/3z=1/21 | | 50=5ln(3x+7) | | 84=2*35+2*w | | X(8-1)=18 | | -1=2x-8 | | -x/4-5=-8 | | -15+t=20 | | 4/3m=8/15 | | a/3-7=10 | | 25x+2000=2000 | | -7(2-6x)-4x=23+x | | -2+3=-(x+6) | | 84+36=93 | | 3*x+sqrt(3)=3*sqrt(3) | | 1/10=1/5y | | 2f-3=11f-24 |